The Development of Flashcard Media for Improving Early Reading Skills in Kindergarten - Purnamasari Marifuddin; Herlina; Muhammad Yusri Bachtiar; Muhammad Akil Musi; Salma Samputri (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2025)
Early reading ability is essential for children’s literacy development; however, observations at Kemala Bhayangkari Kindergarten in Polewali Mandar reveal that many children still struggle to recognize letters, sounds, and simple words. This study aims to develop flashcard media equipped with an audio-reading device to improve early reading skills and to test its validity, practicality, and effectiveness. Using a Research and Development (R&D) design with the ADDIE model, the study involved expert validation, teacher response questionnaires, observations, and assessments of children’s reading abilities. The results indicate that the flashcard media is “Very Valid” (88.8%), “Very Practical” (93.1%), and “Very Effective” (91.2%). The media significantly enhanced children’s ability to recognize, categorize, and pronounce English word cards. These findings align with Vygotsky’s scaffolding theory, Piaget’s preoperational development, behaviorist reinforcement, and multimodal learning principles. Overall, the flashcard media provides an interactive and engaging learning experience and serves as an effective tool to support early reading development in early childhood education.